Influence of standardized ileal digestible tryptophan:lysine ratio on growth performance of 13- to 21-lb nursery pigs - Nitikanchana, S.; Nemechek, J.E.; Usry, J.; Tokach, Michael D.; DeRouchey, Joel M.; Goodband, Robert D.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2012)
A total of 255 nursery pigs (PIC 327 × 1050, initially 13.8 lb and 3 d postweaning) were used in a 28-d growth trial to determine the minimum standardized ileal digestible (SID) tryptophan:lysine ratio for 13- to 21-lb pigs. A 2-phase diet series was used with treatment diets fed from d 0 to 14 and a common diet fed from d 14 to 28. The 6 SID tryptophan:lysine ratios were 14.7, 16.5, 18.4, 20.3, 22.1, and 24.0%. Pigs were allotted on d 3 after weaning with 6 or 7 pigs per pen and 7 replications per treatment. Weight and feed disappearance were determined on d 0, 7, 14, 21, and 28 to calculate ADG, ADFI, and F/G. From d 0 to 14, increasing SID tryptophan:lysine ratio improved ADG (linear, P = 0.02) and generated a tendency for improved ADFI and F/G (linear, P = 0.06 and quadratic, P = 0.08, respectively). Although ADG and ADFI were linear, the greatest response was observed at a SID tryptophan:lysine ratio of 20.3%. From d 14 to 28, when the common diet was fed, ADFI increased (linear, P = 0.05) as SID tryptophan:lysine ratio increased in the previous period, but no differences were found in ADG and F/G. For the overall trial (d 0 to 28), ADG and ADFI increased (linear, P = 0.02 and P = 0.03, respectively) with increasing SID tryptophan:lysine ratio, with the greatest response observed at 20.3%. Feed/gain was unaffected by SID tryptophan:lysine ratio. Thus, the optimal SID tryptophan:lysine ratio for 13- to 21-lb nursery pigs in this study appears to be at least 20.3%. This ratio is greater than the minimum ratio currently using in many practical diet formulations in the United States, indicating an importance of tryptophan in diet formulation of low-protein amino acid-fortified diets in the swine industry.
Keywords: Swine; Amino acid ratio; Lysine; Tryptophan; Nursery pig